فعالية تدعيم الجوائز البيتونية لمقاومة القص - غالية, رامية (Latakia University Journal -Engineering Sciences Series, 2018)
تعتبر الجوائز من أهم العناصر البيتونية الحاملة, تلزم تقويتها عند عدم كفاية المقطع البيتوني, أو عدم كفاية حديد التسليح أو زيادة الأحمال, أو نتيجة صدأ سطحي في التسليح الخارجي أو صدأ في حديد التسليح الداخلي, أو غيرها من الأسباب الأخرى التي سنذكر منها ما تحتاجه هذه الدراسة. إن تضرر العناصر الانشائية وعدم قدرتها على أداء وظيفتها بالشكل الكامل نتيجة تعرضها لعوامل بيئية مختلفة تخرب موادها وتؤدي لانخفاض مقاومتها, أو بسبب وجود عيوب تنفيذية أو الاستثمار غير الملائم لها يؤدي إلى الحاجة إلى إعادة تأهيلها بالصيانة والاصلاح أو التدعيم. لذلك تم اللجوء للتقوية إما بتكبير المقاطع أو التزويد بالتسليح اللازم أو الربط بالصفائح الخارجية الفولاذية المثبتة جيداً إلى المقطع البيتوني وبسبب صعوبة تنفيذها تركزت الدراسات في الآونة الأخيرة على استخدام مواد أكثر فاعلية وهي البوليميرات المسلحة بالألياف. وسنعرض هنا لطرق التدعيم على القص وصولاً إلى الدراسات العالمية التي قامت بالتدعيم على القص باستخدام هذه المواد من البوليمرات والتي تتميز بالمقاومة العالية على الشد والمقاومة الكبيرة للعوامل والظروف البيئية والجوية وسهولة التطبيق في المواقع المحددة على الجائز. Beams are considered as one of the most loaded concrete elements, which needs to be strengthened either as a result of insufficient of concrete section, or insufficient rebar or increased loads, or the result of a superficial steel or corrosion of internal steel reinforcement, and other reasons that we will mention them what we need to study this. The damaged structural elements and their inability to function fully as a result of exposure to different environmental factors damage materials and lead to lower resistance, or because of the existence of of an executive defects or inappropriate investment for its, leads to the need to rehabilitate maintenance and repair or reinforcement. So it was resorting to strengthen either magnify sections or supply necessary reinforcement or steel platelets linking external supported well to concrete section, and because of the difficulty of execution the recent studies has been implemented on the use of more efficient material which is concentrated fiber reinforced polymers. We will present here to methods of strengthening the shear up to the global studies conducted using these materials from polymers, which are characterized by high resistance to tensile and large resistance to environmental factors and weather conditions and ease of application in the specified permissible sites.